2016
DOI: 10.4314/ahs.v16i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices related to sexually transmitted infections among women of reproductive age living in Katanga slum, Kampala, Uganda

Abstract: Background: Sexually transmitted infections (STIs) still stand as one of the commonest health problems affecting women of reproductive age. The knowledge and practices of STIs, among susceptible populations such as women of reproductive age, living in slums like Katanga in Kampala Uganda need to be established. Methods: This was a cross-sectional study with 339 participants in Katanga slum. Data was collected using an interviewer administered questionnaire, entered and analysed using SPSS version 17.0. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
7
14
0
Order By: Relevance
“…In this study, we found that the prevalence of STIs among youths was high, with the highest prevalence found among youths 20-24 years old. This is consistent with several studies (21)(22)(23)(24)(25) showing that the prevalence of STIs was higher among young people aged 20-24 years compared to those 15-19 years. Surprisingly, the prevalence of STIs in 2011 is strikingly higher than in other years.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that the prevalence of STIs among youths was high, with the highest prevalence found among youths 20-24 years old. This is consistent with several studies (21)(22)(23)(24)(25) showing that the prevalence of STIs was higher among young people aged 20-24 years compared to those 15-19 years. Surprisingly, the prevalence of STIs in 2011 is strikingly higher than in other years.…”
Section: Discussionsupporting
confidence: 93%
“…Seven included studies assessed the awareness of 2,986 Africans in regard to STIs as general, three studies were conducted in Nigeria [17,18,44] and one in each of Madagascar, Morocco, Mali, Uganda [47,56,70,71] . The oldest among the study included was conducted after 2010 while the newest was conducted in 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Amu and colleagues provided more specific information in regard to source of knowledge as they determined that there are three major sources of information; the radio and television 343 (68.7%); teachers 340 (68.1%); and newspapers 224 (44.9%). Nevertheless, Nawagi and colleagues in their study in Uganda determined that only (23.9%) of the participants have information about STIs from the media [17,47,56] .…”
Section: Resultsmentioning
confidence: 99%
“…Sevenincluded studies assessed the awareness of 2,986 Africans in regard to STIs as general, three studies were conducted in Nigeria [17,18,44] and one in each of Madagascar, Morocco, Mali and Uganda [47,56,70,71]. The oldest among the study included was conducted after 2010 while the newest was conducted in 2014.…”
Section: Sexually Transmitted Infections (Stis)mentioning
confidence: 99%
“…Amu and colleagues provided more specific information in regard to source of knowledge as they determined that there are three major sources of information; the radio and television 343 (68.7%); teachers 340 (68.1%); and newspapers 224 (44.9%). Nevertheless, Nawagi and colleagues in their study in Uganda determined that only (23.9%) of the participants have information about STIs from the media [17,47,56]. Joda and his colleagues in Nigeria conducted a study to assess the level of knowledge of STIs among students from different schools and concluded that there is no statistically significant differences in the responses obtained from various schools.…”
Section: Sexually Transmitted Infections (Stis)mentioning
confidence: 99%